An Analysis of Illocutionary Acts Found in Aespa Speech at the United Nation - Hasyifa Diffani; Harisna Hikmah (Universitas PGRI Yogyakarta, 2023)
A speech consisting of spoken sentences represents an utterance and contributes to the overall message being conveyed. We use utterances in action, known as speech actions, in communication. K-pop girl group Aespa in 2022 was invited by the United Nations High-Level Political Forum to give a speech. This study is aimed to determine the speech acts types used by Aespa and to find out the function of the speech acts. To collect the data, the researchers transcribed the data comprehensively, which were analyzed using descriptive qualitative research based on the type of speech. The finding data showed 18 utterances with illocutionary acts. Those are 12 representative utterances, 1 directive utterance, 4 expressive utterances, and 1 commissive utterance. It implies that representative are preferred than the other type of illocutionary acts. It contributes to the understanding of how popular culture, specifically K-pop, can be harnessed as a platform for social advocacy and meaningful discourse on global issues. It contributes to the spread of the message.